2002
DOI: 10.1046/j.1365-313x.2002.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function of a rice brassinosteroid biosynthetic enzyme, C‐6 oxidase, prevents the organized arrangement and polar elongation of cells in the leaves and stem

Abstract: Summary Molecular genetic and physiological studies on brassinosteroid (BR)‐related mutants of dicot plants have revealed that BRs play important roles in normal plant growth and development. However, little is known about the function of BR in monocots (grasses), except for the phenotypic analysis of a rice mutant partially insensitive to BR signaling. To investigate the function of BR in monocots, we identified and characterized BR‐deficient mutants of rice, BR‐deficient dwarf1 (brd1). The brd1 mutants showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
357
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 326 publications
(374 citation statements)
references
References 35 publications
14
357
0
3
Order By: Relevance
“…This suggests that in grape berries the main bioactive BR is likely to be CS, and the conversion of 6-DeoxoCS to CS (catalyzed by the VvBR6OX1 gene product) may be an important BR activation step in this species. This scenario is similar to the reported situation in vegetative tissues of tomato (Yokota, 1997;Bishop et al, 1999) and rice (Hong et al, 2002), where CS is considered to be the main bioactive BR. However, in many circumstances BL is thought to be the major bioactive BR.…”
Section: Insights Into Br Biosynthesis In Grapesupporting
confidence: 88%
“…This suggests that in grape berries the main bioactive BR is likely to be CS, and the conversion of 6-DeoxoCS to CS (catalyzed by the VvBR6OX1 gene product) may be an important BR activation step in this species. This scenario is similar to the reported situation in vegetative tissues of tomato (Yokota, 1997;Bishop et al, 1999) and rice (Hong et al, 2002), where CS is considered to be the main bioactive BR. However, in many circumstances BL is thought to be the major bioactive BR.…”
Section: Insights Into Br Biosynthesis In Grapesupporting
confidence: 88%
“…Microscopy inspection of dark-green leaves revealed that the number of bulliform cells was increased in the mutants when compared with wild-type plants ( Figure 2B). An increase in the number and size of bulliform cells is also observed in BR-deficient dwarf1 (brd1) rice mutants (Hong et al, 2002). In addition, the other ravl1 phenotypes (i.e., late germination, retarded shoot growth, and dark-green leaves) are also often found in BR-related mutants (Yamamuro et al, 2000;Hong et al, 2003).…”
Section: Br-related Phenotypes Of Ravl1 Mutants and Overexpressorsmentioning
confidence: 99%
“…To date, several rice mutants with altered leaf inclination or QTLs related to lamina joint angle have been genetically identified [3,[7][8][9][10], and the major detected QTL for leaf angle is tiller angle 1 (ta1) [7,8]. However, the underlying mechanism of the leaf angle alteration has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Rice lamina joint angle increases proportionally to BR levels [11,12], and deficiency of OsDWARF4, a key gene in BR biosynthesis, resulted in increased leaf erectness and enhanced grain yields in dense planting [3]. The erect leaves were also observed in other BR biosynthesis-defective mutants including ebisu dwarf (d2, deficiency of CYD90D2/D2 [10]) and brassinosteroid-deficient dwarf1 (brd1, deficiency of OsDWARF [9]). In addition, the BR signaling-defective mutant d61-7, the weakest mutant of rice BRASSINOSTEROID INSENSITIVE1 (OsBRI1, a protein kinase severing as rice BR receptor), and transgenic rice plants with suppressed expression of OsBZR1 (a transcription factor involved in BR signaling pathway), showed erect leaves [13][14][15].…”
Section: Introductionmentioning
confidence: 99%